Suitability analysis of solar tracking PV system in the airport based on glare assessment - Sreenath, S.; Sudhakar, K.; Ahmad Fitri, Yusop (Universiti Malaysia Pahang, 2021)
Due to the concerns with harmful emissions, airports have a great interest in solar photovoltaic technology. On the one hand, the vacant land areas in the airport can house solar PV arrays. On the other hand, there is an aviation safety issue due to the reflections from the solar PV arrays. This paper aims to perform a glare analysis of a conceptual solar PV array for three different solar tracking techniques. This suitability analysis is carried out for fixed-tilt, single-axis and dual-axis tracking techniques using ForgeSolar software. It is observed that a single-axis tracking solar PV system is a suitable tracking technique for the selected site. This can be attributed to zero minutes of glare duration and the highest value of energy generation. In addition to compliance with the FAA’s solar glare policy, the single-axis tracking solar PV system will generate 40 % more electricity than a fixed-tilt solar PV system. Unlike previously reported studies, the results of this study strengthen the theoretical support for tracking solar PV systems in airport locations. The findings provided in this study will be beneficial to energy professionals and serve as reference material for tracking solar PV in airports.